Temporal variation in composition, abundance and biomass of the fish fauna after impact on subtropical transitional water - Afonso, Maíra Gnoatto; Cattani, André Pereira; Bot Neto, Renato Luiz; Cardoso, Olímpio Rafael; Spach, Henry Louis; Schwingel, Paulo Ricardo (Acta Scientiarum. Biological Sciences, 2023)
Transitional waters are characterized by large variations in salinity, temperature, turbidity, among other factors, such as tidal cycle, wind action and rainfall, that are constantly changing over time. The distribution of biota in these environments is regulated by these natural variations and also by human activities, such as pollution, overexploitation of resources, acceleration of urbanization, suppression of habitats and changes in hydrological dynamics. The objective of this study was to analyze the temporal dynamics of the fish fauna of the Saco dos Limões Cove, state of Santa Catarina, Brazil, after the construction of a highway. Fish community was evaluated over five years by annual and monthly variation in species richness, abundance and biomass. A total of 17,993 individuals were collected, distributed in 33 families, 59 genera and 79 species. The evaluated years were similar to each other in species composition. Community descriptors varied over time but did not show seasonal trends. In all years, abundance was higher than biomass, indicating both the disturbance and the ecosystem function as a nursery in the studied area. This was corroborated by the large number of juveniles of dominant species (Genidens genidens, Eucinostomus gula and Eucinostomus argenteus).